The northern limit of Alnus (Fagales) in Costa Rica: modern pollen evidence of a possible range extension - Horn, Sally P.; Rodgers, John C. (Revista de Biología Tropical, 1996)
The genus Alnus is represented in Costa Rica by one species. Alnus acuminara H.B.K.. a 5-20 m tall tree characteristic of montane forest formations (Furlow 1977). Burger (in Janzen 1983) stated that in Costa Rica A. acuminata is not known to occur north of Volcán Barva in the Cordillera Central. even though the species ranges northward to Mexico. However. Hartshorn and Poveda (in Janzen 1983) and Haber (1990) report A. acuminata to be present within the Monteverde reserve in the Cordillera de Tilarán (one range northwest of the Cordillera Central). According to Haber (1990), the species occurs as low as 90 m on the Atlantic slope, in the Río Peñas Blancas valley (approximate coordinates loo22’N, 84°38’W).